New Commuting Zone delineation for the U.S. based on 2020 data - Christopher S. Fowler (Scientific Data)
Abstract This paper documents the creation of new ‘commuting zones’ for the United States based on 2020 geographies and data. Commuting zones originated in the late 1980’s as the result of an effort by the Economic Research Service of the U.S. Department of Agriculture to provide a county-based delineation of functional regions that covered the entire U.S. and linked rural areas to their nearest economic center. The commuting zones presented here update the 2010 era definitions. Additionally, this new delineation incorporates measures of quality to facilitate comparison with earlier decades and to account for the fact that the quality of commuting-based delineations may have been substantially affected by changing patterns of work and residence during and after the covid-19 pandemic. The methodology used here seeks to replicate as nearly as possible the method employed in earlier versions of this delineation using hierarchical clustering on a proportional flows matrix generated from county to county commuting flows. The data and all scripts used to generate them and this paper are available at https://github.com/csfowler/CommutingZones2020.git .